Pengaruh Motivasi Intrinsik Dan Ekstrinsik Terhadap Kinerja Pelatih Taekwondo Di Lingkungan Pengcab TI Kabupaten Bandung Barat - Alrifni, Seftia; Apriadi, Deri (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Analyzing the impact of both internal and external motivation on the performance of Taekwondo instructors at the Pengcab TI (Taekwondo Indonesia Branch Board) in West Bandung Regency is the goal of this study. Athletes' technical proficiency, self-control, and performance are all greatly enhanced by their coaches. The success of a coach is thought to be significantly influenced by motivation, which can be both extrinsic (such as rewards from outside sources and organizational support) and intrinsic (such as self-satisfaction and a sense of duty). Thirty Taekwondo instructors in the area participated in the survey, which was used in this quantitative study. Every item on the questionnaire is valid and reliable, according to the findings of validity and reliability testing. Although the association was negative, correlation and regression analysis revealed that neither intrinsic nor extrinsic motivation had a significant impact on coach performance. This implies that coach performance may be more heavily influenced by other outside variables. It is anticipated that the results will aid in the creation of sports management techniques, specifically in improving taekwondo coaching effectiveness.